PENGGUNAAN APLIKASI QGIS UNTUK PEMBUATAN PETA TATA GUNA LAHAN DI KECAMATAN BUKITKECIL - Pironika, Tarisa; Wahab, Wahyuni (Ensiklopedia Research and Community Service Review, 2025)
Bukitkecil District is one of the rapidly developing areas in Palembang City, South Sumatra, with various land uses. Therefore, accurate data regarding land use is needed to plan the management and utilization of natural resources sustainably. One of the tools that can be used to produce land use maps is QGIS (Quantum GIS) software, which is an open-source Geographic Information System (GIS) application. This research aims to use QGIS for creating land use maps in Bukitkecil District, using spatial and non-spatial data to visualize existing land use. The resulting map is expected to be used as basic information in decision-making and spatial planning in the Bukitkecil District area.Keywords:QGIS,Land Use,Map,Geographic Information System (GIS),Bukitkecil District